Práticas de saúde coletiva realizadas pelos profissionais de saúde do Programa de Saúde da Família de Alagoinhas – Bahia - Silva, Emanuela Cardoso da (2009)
This study on the activities of Public Health conducted by the Family Health Team (ESF) in Alagoinhas - BA aims to examine the practice of Public Health carried out by health care professionals who work at the Family Health Program in Alagoinhas (PSF) - Bahia. Its specific objectives are to identify the activities of Public Health carried out by health care professionals who work in the PSF; to characterize ways of working used by professionals who work in the PSF and to identify the purpose in the practice of public health made by health care professionals who work in the PSF. The methodological strategy is descriptive of a qualitative nature. The data collection techniques used was the semi-structured interviews and participant observation. Study subjects were professionals of the ESF, including the surgeon-dentist. Data analysis was guided by the plan of analysis. The results show that the most of the activities that are classified as public health were conducted by all team members. The activities are related to control of causes, risks and damage, except for health monitoring activities, the activities of planning and management in health also occur, but the territory is held by ACS, the other activities are shared by the team members, leaving it to the coordinator to supervise the team, taking responsibility for resources and materials for meetings of the team. The study also showed that the educational activities are constant, especially in groups and in general without the participation of nursing techniques. The working class emerged in the social relations of the empirical field, demonstrating that there is interaction between team members and when necessary the collaboration between them. The instruments used to perform most activities are maps, spreadsheets, forms, record books,lectures, meetings, among others. The team in general, is used in search of knowledge and multidisciplinary training and constant updating. The aims are achieved: knowledge of the population and territory, but in no systematic way, based more on everyday findings of the team, liaison with government agencies and non-governmental and stimulation of social control through the CLS. The research enabled us to correlate the theory used to support the study, showing how the public health has been established as a broad field of knowledge and practices and are put into practice every day by the subjects operating in the SUS. We agree that the (re) organization of the AB is a condition sine quo non for the re-establishment of tangible goals that can actually cause changes in health status of our country.